The Lancashire cotton industry and its rivals international competition in cotton goods in the late nineteenth century : Britain versus India, China, and Japan - Kawakatsu, Heita 1948- (LTCB international library selection, 2018)
The study based on his original research, undertaken in Oxford and subsequently in Japan, covers the important nexus established between Japan and the United Kingdom in the nineteenth century with the export of cotton textiles (of higher quality) from Britain to Asia. This historical link between key industries in our two countries is now happily mirrored in current scholarship, of which this is a prime example. It is no function of a brief preface to replicate the conclusions of detailed research but to emphansize the sider context of the research which lies behind the text of this book, which I am most happy to endorse. -- Jacket.